Burning Frequency Influences Plant Composition and Diversity and Mycorrhizal Spore Density in a Lateritic Dry Deciduous Sal Dominated Forest - Bhaumik, Suvashree; Kar, Manu; Dutta, Somshubhra; Ghosh, Somdatta (Research in Ecology, 2024)
Abstract: Burning in forest floor, specially, in deciduous forests is an annual practice of forest dwellers in some states of India to collect non timber forest produce at ease. Sometimes this springtime burning get out of control and damage the forest severely. Sal dominated mixed forest in Godapyasal range, Midnapore division, West Midnapore in south West Bengal, with different fire incidence histories was taken for the study. An intensive survey of sites with regular burning, occasional burning and no burning were done to study plant diversity and community composition and the results were compared within different sites. Severe burning regimes damaged the plant density drastically rendering the saplings of subdominants only near ground level as coppice. Mild fire frequencies, though not severely damaged plant community, differed from unburned area significantly. Fire hardy tree species are dominant and subdominant in both sites. In severe burned site, plant diversity increased with a number of invasive perennials and annuals and spiny undershrubs and show even distribution. Common plants in the three communities were observed to be affected in their community parameters with burning frequency. Frequent and occasional burning both reduced mycorrhizal population with larger spores drastically and not replaced even after nine months of burning. AMF with smaller spores are less affected.